DOP69 Glycans as an actor in the microbiome-immune response crosstalk. (30th January 2023) - Rodrigues, C; Gaifem, J; Pereira, M; Lavelle, A; Colombel, J F; Sokol, H; Pinho, S
Abstract: Background: The perturbation of the symbiotic relationship between microbes and the intestinal immune system contributes to Inflammatory Bowel Disease (IBD) development even years before diagnosis. However, the causes underlying the loss of gut microbial equilibrium (dysbiosis) associated with inflammation still remain unknow. The host glycocalyx (repertoire of glycans/sugar-chains at the surface of gut mucosa) constitutes a major biological interface between gut mucosa and microorganisms 1 . In this study we aimed to evaluate whether and how an altered host glycome perturbs microbiome composition associated with dysbiosis and initiation of intestinal inflammation. Methods: We have modulated the glycosylation profile at the level of gut mucosa using specific glycoengineered mouse models (KO) that exhibit specific alterations (deficiencies) in glycosylation composition. Colitis was induced using DSS and microbiome analysis was performed by 16S rDNA sequencing both in WT and KO mice. The mucosa glyco-immunoprofile was characterized. Results: We first demonstrated in different glycoengineered mice that changes in the composition of glycans at gut mucosa resulted in dysbiosis characterized by a significant decrease in beneficial members of the Firmicutes phylum compared with WT mice. These mice with deficiency in mucosa glycosylation exhibited a higher susceptibility to colitis 2 . Then, and to determine the causal effect of mucosa glycosylation-induced microbiota modulation, we co-housed KO and WT mice. After 5 weeks of cohousing with WT mice, the KO mice exhibited a much less severe colitis and an increased proportion of bacteria from Firmicutes phylum compared to single housed KO mice. Inferred metagenomics analysis further revealed an alteration of the glycosylation biosynthetic pathway that was apparently shared and gained upon co-housing the KO mice with WT. The analysis of colonic inflammatory infiltrate from cohoused KO mice showed an increased expression of IL17 and IL22 production in gut mucosa, at baseline and before DSS. This pinpoints a potential protective effect of the enhancement of glycosylation biosynthesis (through microbiome sharing with WT) for preventing dysbiosis and dysregulation of gut immune response. Conclusion: In this study, we demonstrate that changes in composition of glycans at the gut mucosa level is associated with dysbiosis and susceptibility to colitis. These results illustrate the relevance of the gut glycome in shaping the gut microbiota, highlighting its role in maintaining a homeostatic crosstalk between the microbiome and host immunity. This study was funded by ECCO Pioneer Award. 1. Verhelst, Gastroenterology 2020. PMID: 31626754 2. Dias et al PNAS 2018 PMID: 29720442